2018
DOI: 10.15625/2525-2518/54/2a/11906
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Hazard of Polycyclic Aromatic Hydrocarbon in Road Dust in Ha Noi Metropolis

Abstract: This study investigates PAHs content in road dust of Hanoi metropolis, Vietnam. The samples were colected from the roads around city and analyzed by gas chromatography mass spectrometry (GC/MS). The total PAHs mass concentration ranges from 33.88 µg/kg to 5588,16 µg/kg, with the mean of 356,24 µg/kg in which HMW accounted up 70 % and LMW made up 30 %. The toxic equivalence factors (TEFs), mutagenic potency equivalent factors (MEFs) and the incremental lifetime cancer risk (ILCR) methodologies were applied to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The approaches distinguish anthropogenic multiple releases chiefly from petroleum and other sources [20,9]. BaP is widely accepted as the indicator for measurement of carcinogenicity, thus BaP-equivalent toxicity for other carcinogenic PAHs has been recommended [31,2] and evaluated for cancer risk assessment [21,5,24,30].The result showed that BLCO contained greater percentage mean of 8PAH than 16PAH and was less carcinogenic than mutagenic to exposed group of C. gariepinus. There is greater need for further investigation of the biochemistry and physiology on the mutagenic effects to fish, animals and humans alike that consume them given its high responses on the experimental fish to BLCO in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…The approaches distinguish anthropogenic multiple releases chiefly from petroleum and other sources [20,9]. BaP is widely accepted as the indicator for measurement of carcinogenicity, thus BaP-equivalent toxicity for other carcinogenic PAHs has been recommended [31,2] and evaluated for cancer risk assessment [21,5,24,30].The result showed that BLCO contained greater percentage mean of 8PAH than 16PAH and was less carcinogenic than mutagenic to exposed group of C. gariepinus. There is greater need for further investigation of the biochemistry and physiology on the mutagenic effects to fish, animals and humans alike that consume them given its high responses on the experimental fish to BLCO in the present research.…”
Section: Discussionmentioning
confidence: 99%